(3TQM GdebfY TQM defXheI eMeO Hf SYjO GdeSeGI HGdebfYs - (3GdhQRGRj, CMeO Hf eMeO Hf YHO Gddg, J(B1179(3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf edLC GdePfHjf GdNGFajf eLjH OYhI GdeVWQjf Rjf GdSeGA HGdfLhe GdRGgQGJ djgJOj HgG Edi GdChbGJ hjSJOd HgG Ydi GdLgGJs
(3BNQgG (B:s
(3fGbU GdBNQ, hBNQg(B: (3hbjd eCNhP ef GdTjW GdPj gh GdgdGc (B() (3EPG gdc hSej HGdTjWj Ydi gPG dgdGcg Ydi eYUjI dCfg GeJfY ef GeJKGd CeQ Gddg JYGdi HGdSLhOs
(3fSNI efbhdI ef fSNI GdeDda GdeDQNI SfI (B1164(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: 1 / 277s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3gjFIs